2002
DOI: 10.1063/1.1529088
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor behavior of PbxBi4Ti3+xO12+3x (x=2,3) Aurivillius ceramics

Abstract: The relaxor response of the PbxBi4Ti3+xO12+3x (x=2,3) Aurivillius ceramics is reported. The relaxor behavior appears with an increase of the symmetry in the ab plane of the structure and a decrease of the transition temperature. By the application of a bias field on nonpoled samples, it is possible to induce the piezoelectric response. The piezoelectric coefficient in the planar mode of −72 pC/N was measured at 210 °C for Pb2Bi4Ti5O18 ceramic disks. These results represent a step in the search of high-temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
1
14
0
1
Order By: Relevance
“…The broad peak, the ferroelectric ordering temperature (T c ), is attributed to the disorder of Pb and Bi atoms in the Bi 2 O 2 layers and in the perovskite layers as described for PbBi 2 Nb 2 O 9 [30]. The (T c ) peaks of Pb 1 À x Bi 4 þ x Ti 4 À x Mn x O 15 resemble the observations by Fernandez et al [3] (808 K) and are slightly lower than the value reported by Subbarao [2] (843 K) and Ikezaki et al [29] (823 K) both for composition of PbBi 4 Ti 4 O 15 . However, the sample x ¼0.6 exhibits a peak at higher temperature (850 K).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The broad peak, the ferroelectric ordering temperature (T c ), is attributed to the disorder of Pb and Bi atoms in the Bi 2 O 2 layers and in the perovskite layers as described for PbBi 2 Nb 2 O 9 [30]. The (T c ) peaks of Pb 1 À x Bi 4 þ x Ti 4 À x Mn x O 15 resemble the observations by Fernandez et al [3] (808 K) and are slightly lower than the value reported by Subbarao [2] (843 K) and Ikezaki et al [29] (823 K) both for composition of PbBi 4 Ti 4 O 15 . However, the sample x ¼0.6 exhibits a peak at higher temperature (850 K).…”
Section: Resultssupporting
confidence: 67%
“…It can be noted that the dipole moment from Ti(1)O 6 displacements is close to zero for xZ0.4, indicating a small contribution from this layer. In the Aurivillius phases with Pb x Bi 4 Ti 3 þ x O 12 þ 3x series, the T c is found to increase as the number of perovskite layer decreases [2,3]. Presumably increasing T c in Pb 1 À x Bi 4 þ x Ti 4 À x Mn x O 15 can be caused by a decrease of the contribution of the inner Ti(1)O 6 octahedra and a larger contribution of more distorted outer Ti(2)O 6 octahedra.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Since its discovery by Aurivillius in 1949 [4], Bi 4 Ti 3 O 12 has attracted considerable attention due to its high Curie temperature of about 675 • C [5][6][7]. Many BLSF with m = 4 or 5 can also be derived from Bi 4 [8][9][10][11][12][13][14]. Recently, structural investigations on the Bi 4 Ti 3 O 12 + xNa 0.5 Bi 0.5 TiO 3 system have revealed that the bismuth layer-structured Na 0.5 Bi 4.5 Ti 4 O 15 phase and the perovskite Na 0.5 Bi 0.5 TiO 3 phase are prone to reject each other in their solid solution [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to making quantitative predictions for cation exchanges in phases of the (Bi 2Àx Pb x O 2 )(Pb y Bi 1Ày ) nÀ1 B n O 3n+1 type, the model can be used to explain qualitatively the inexistence of phases with a high value of n. In the isoestructural series as Pb nÀ3 Bi 4 Ti n O 3n+3 , for example, only phases with n 7 are reported [3,34]. In these materials, the cation exchange should contribute to the phase stability.…”
Section: Discussionmentioning
confidence: 98%